Mechanism and Application of Static Fracturing Technology on Deep Working Face. (13th May 2021) - Cui, Feng; Lei, Zhaoyuan; Cheng, Xiaoqiang; Wu, Xueming; Shan, Pengfei; Lv, Zhaohai
Abstract : Static fracturing technology uses chemical expansion agents to fracture roofs. With the aim of fracturing corner roofs on deep working faces, in this study, the static fracturing technology was investigated through theoretical analysis, laboratory experiments, numerical calculations, and field practice. The theoretical analysis and experiments demonstrated that the swelling force increased with a decrease in the fracturing hole spacing, and the optimal water-cement ratio was 0.33. Twelve groups of FLAC3D models were designed using SPSSAU. The results revealed that the optimal fracturing effect was achieved when the hole diameter was 60 mm, hole spacing was 40 cm, and hole depth was 6 m. The fracturing effect of hard corner roofs was monitored by peering into the borehole and evaluating the support resistance. Thus, it can be concluded that within the fracturing range, internal fissures in the rock stratum are developed and linked to each other. The support pressure was the highest, 7 h after grouting, with a value of approximately 26.1 MPa, and then decreased gradually to 17.58 MPa, indicating that the static fracturing technology attained the expected results.